Children’s Literature and Translation Under the East German Regime - Thomson-Wohlgemuth, Gabriele (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis paper describes the status of translation and publication of East German children’s literature during the period of the Cold War. It briefly gives an indication of the high value placed on translation and translators in the socialist regime. Finally it focuses on the main criteria influencing the translation and publication of children’s books with the economic and ideological factors being the most significant and gives brief examples from the East German censorship files.